2011
DOI: 10.1111/j.1537-2995.2010.02769.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of perioperative intravenous iron therapy in elderly hip fracture patients: a single‐center randomized controlled trial

Abstract: Transfusion requirements in patients with intracapsular fracture or baseline Hb level of 12 g/dL or more appear to be reduced by IV iron sucrose therapy, but there was no difference in morbidity, mortality, or length of hospital stay. The treatment is safe and hastens recovery from blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
159
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(166 citation statements)
references
References 38 publications
4
159
1
1
Order By: Relevance
“…No standard dose exists in this setting; however, total doses of 200 to 600 mg of iron sucrose (100-200 mg every 48 hours for 2-3 doses beginning on the day of admission) perioperatively have been reported in studies focusing on IV iron. [26][27][28][29][30][31] Studies typically did not report baseline iron labs; however, 1 trial specified that patients had nearnormal iron levels (46.3-53.2 µg/dL), with no significant difference between groups as well as normal ferritin and transferrin levels. 26 No difference has been shown in blood transfusion rates (percentage of patients receiving a transfusion) in studies that compared patients receiving IV iron alone administered throughout the preoperative and postoperative periods with patients not receiving iron.…”
Section: Perioperative Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…No standard dose exists in this setting; however, total doses of 200 to 600 mg of iron sucrose (100-200 mg every 48 hours for 2-3 doses beginning on the day of admission) perioperatively have been reported in studies focusing on IV iron. [26][27][28][29][30][31] Studies typically did not report baseline iron labs; however, 1 trial specified that patients had nearnormal iron levels (46.3-53.2 µg/dL), with no significant difference between groups as well as normal ferritin and transferrin levels. 26 No difference has been shown in blood transfusion rates (percentage of patients receiving a transfusion) in studies that compared patients receiving IV iron alone administered throughout the preoperative and postoperative periods with patients not receiving iron.…”
Section: Perioperative Settingmentioning
confidence: 99%
“…[26][27][28][29][30][31] Studies typically did not report baseline iron labs; however, 1 trial specified that patients had nearnormal iron levels (46.3-53.2 µg/dL), with no significant difference between groups as well as normal ferritin and transferrin levels. 26 No difference has been shown in blood transfusion rates (percentage of patients receiving a transfusion) in studies that compared patients receiving IV iron alone administered throughout the preoperative and postoperative periods with patients not receiving iron. [26][27][28] Conversely, a retrospective study focusing only on postoperative IV iron administration found that its use significantly reduced the percentage of patients receiving a transfusion (11.5% vs 26.4%, P = 0.001).…”
Section: Perioperative Settingmentioning
confidence: 99%
“…They compared iron sucrose in hip fracture patients with no iron suppletion and found reduced transfusion requirements in patients with intra-capsular fractures and in those with hemoglobin levels of 12g/dl or more if given 600 mg intravenous iron during the operation (Serrano-Trenas et al, 2011),. They found no difference in mortality, morbidity or length of hospital stay, however (Serrano-Trenas et al, 2011).…”
Section: Ironmentioning
confidence: 99%
“…iron + rHuEPO group, respectively). The largest randomized trial compared IS treatment (3 times 200 mg iron at 48 h intervals starting at the day of admission) and standard clinical management in 200 patients undergoing hip fracture repair surgery (no patient received EPO) [74]. In the overall population, there was no significant difference in transfusion requirements, length of stay, morbidity and mortality between the two groups.…”
Section: Perioperative Iron Treatmentmentioning
confidence: 99%
“…iron products). Among the 36 published clinical studies [45][46][47][48][49][50][55][56][57][58][59][60]64,65,70,74,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91] that are included in the clinical dossier of Venofer, 26 reported at least some details about adverse drug events; 3 of those reported at least possibly related serious adverse events (all nonfatal, Table 2) [51,76,77]. Three reports included only general statements on safety without further details (e.g., no serious adverse reactions were noted) [47,48,64].…”
Section: Safety and Tolerabilitymentioning
confidence: 99%